The Tarekat Network and Political Determination of Nahdlatul Ulama - Jamil, M. Mukhsin (JURNAL PENELITIAN, 2021)
This paper aims to fill the gap in the study of tarekat (Sufi orders) and politics in Indonesia. It specifically wants to reveal the determination of the tarekat network and movement within Nahdlatul Ulama (NU) and their influence on the socio-political dynamics of this organization. The hypothesis that underlies this paper is that tarekat not only has religious potential, but also holds social, political, economic, and cultural potential. Socio-religiously, tarekat becomes a medium for instilling and transmitting religious values; it becomes a transmitter for ethical and spiritual values in society. Meanwhile, institutionally, tarekat is also a vehicle for articulating social interests and power. In this sense, the tarekat figures are not only active in religious activities but also able to form and be involved in the political arena. They created undercurrents to promote democratization and even collaborated with power holders to control political agendas and respond to socio-religious issues. The 2019 electoral political contestation shows that NU has succeeded in becoming the channel for democratic forces when competing with the forces of Islamism. Next, this study also indicates that the tarekat networks, as a force that can gather spiritual and political support, make NU a socioreligious organization that helps determine politics in Indonesia. Using Bourdieu's theoretical framework of social capital, this paper shows that the tarekat movement, as a religious institution in dialectic with social and political situations, will be primarily determined by habitus, capital, and arena. In general, these findings imply that the conception of tarekat often seen as apolitical mysticism needs to be reviewed and reconceptualized since, in fact, it is socio-politically relevant.